A gap-analysis model for identifying effective government support for New Technology-Based Firms (NTBFs) in Thailand - Thanaphol Virasa (2018)
The current paper seeks to analyse the gap in government support for New Technology-Based Firms (NTBFs) in the context of Thailand. To develop an analytical model for focused gap-analysis of government supporting schemes, the author integrated characteristics of NTBFs and various dimensions on entrepreneurial process and technology commercialisation. The related supporting measures for NTBFs in Thailand were identified and analysed by using the proposed model. This paper describes the benefits of this modelling process with suggestions for public interventions on fostering entrepreneurship and innovation. © 2007 Inderscience Enterprises Ltd.